Data Acquisition System of Temperature Measurement Using LabVIEW Application - Mohapatra, Badri Narayan; Barwade, Neilsinh; Walse, Ayush; Patil, Dhairyashil (LPPM Universitas Andalas, 2023)
Data Acquisition (DAQ) is widely used in Research and Development, Quality Control, Testing. Data acquisition (DAQ) is a process in which raw transducer signals are converted to computer readable data so that computers can store and manipulate that data. Temperature control system mainly the measuring and even to achieve stable or desired value have big challenge and importance in all sector of industry. This article tries to summarize the recent advancements in data acquisition technology and also explains the utility of LabVIEW software in DAQ applications related to temperature measurement.